Krukenberg tumor secondary to gall bladder carcinoma masquerading C3 glomerulopathy. Issue 3 (October 2020) - Meena, Priti; Bhargava, Vinant; Rana, Devinder Singh; Bhalla, Anil Kumar; Gupta, Ashwani; Gupta, Pallav
Background: C3 glomerulopathy is caused by dysregulation of the alternative complement pathway. Association with solid organ tumors is rare. However, there have been a few case reports of membranoproliferative glomerulonephritis secondary to gastrointestinal neoplasms. Case: A 38-year-old female presented with abdominal distension, loss of appetite, amenorrhea, and easy fatigability. She had been diagnosed 8 months back with C3 glomerulopathy and had received immunosuppression. On evaluation, she was incidentally detected to have Krukenberg tumor. The primary site of malignancy was gall bladder. Conclusion: Our case report highlights a possible association between C3 glomerulopathy and Krukenberg tumor secondary to gall bladder carcinoma and emphasizes the fact that even in cases of C3 glomerulopathy, occult malignancy should be considered as an underlying pathology.